2019
DOI: 10.1108/jima-04-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effect of customer beliefs on the intention to participate in family Takaful schemes

Abstract: Purpose The purpose of this study is to apply the theory of planned behavior (TPB) in predicting the intention to participate in family takaful schemes (FTSs) in the United Arab Emirates (UAE). One area of concern for takaful operators is their untapped market and lower market share compared to those of their conventional insurance counterparts. It is possible that the investigation of direct and indirect (belief based) measures of TPB could shed some light on these concerns and possibly offer some assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 47 publications
4
31
0
4
Order By: Relevance
“…Past studies conducted by Amin ( 2012 Bhatti and Md Hussin (2020) have shown that the subjective norm relationship with tak aful products' selection is positive and significant. Subjective norm is also a motivating factor for customers' acceptance of a product (Amin et al, 2013(Amin et al, , 2014Ganesan et al, 2020).…”
Section: Subjective Normmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies conducted by Amin ( 2012 Bhatti and Md Hussin (2020) have shown that the subjective norm relationship with tak aful products' selection is positive and significant. Subjective norm is also a motivating factor for customers' acceptance of a product (Amin et al, 2013(Amin et al, , 2014Ganesan et al, 2020).…”
Section: Subjective Normmentioning
confidence: 99%
“…(2016),Aziz et al (2019),Ali et al (2019), Farhat et al (2019,Bhatti and Md Hussin (2020),Hassan and Abbas (2020) andShaikh et al (2020).…”
mentioning
confidence: 99%
“…Sharia bank products, takaful schemes, halal products, etc. (Husin and Rahman, 2013;Rajagopal et al, 2011;Haque et al, 2010;Haque et al, 2015;Rezai et al, 2012;Bhatti and Husin, 2019), while others have looked at what Muslims find offensive in ads as well as at the attitudes of Muslim consumers to the influence of the West (De Run et al, 2010;Farah and El Samad, 2015;Sobh and Belk, 2011). Although studies such as these have looked at the choices that Muslim consumers make in purchasing products or services that are specifically associated with Islam (Razzaque and Chaudhry, 2013;Ariffin et al, 2016;De Run et al, 2010;Bachleda et al, 2014;Mansour and Diab, 2016), our understanding of the role of religious salience, more broadly in purchasing intentions, is still in its infancy (Mathras et al, 2016;Islam and Chandrasekaran, 2016;Butt et al, 2018).…”
Section: Jima 116mentioning
confidence: 99%
“…A search of the literature showed that previous studies focused more on customer intention to participate in takaful from various factors which included mass media, word of mouth, and subjective norms (Maizaitulaidawati et al, 2016;Farhat et al, 2019), attitude, subjective norm, and perceived behavior (Maizaitulaidawati & Asmak, 2013), perception of takaful operators' performance (Haji Wahab, 2018), and customer beliefs (Bhatti & Md Husin, 2019).…”
Section: Introductionmentioning
confidence: 99%